(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The present study was designed to investigate the anthelmintic potential of Amaranthus tricolor Linn plant of Amaranthaceae family using acetone, ethyl acetate and ethanol as solvents. The extracts were screened for phytochemical constituents and evaluated for their vermicidal activity against adult Eisenia fetida earthworms. All the extracts were containing phytochemical, but comparatively, the acetone extract was showing strong presence of most of the phytochemicals and ethanol extract was containing lesser number of phytochemicals. Various concentrations (10–30 mg/ml) of each extract were studied in the bioassay, observing the time of paralysis and death of the earthworms. Albendazole was used as reference standard and normal saline as a control group. All extracts exhibited dose dependent anthelmintic activity in both the parameters (paralysis and death) and were showing more potency than the standard drug. The most promising activity was exhibited by the acetone extract (30 mg/ml) causing the paralysis within 5 minutes and death of worms within 13 minutes. The result suggests that the acetone extract of A. tricolor Linn plant may be useful as an anthelmintic. In the present study, the traditional use of this leafy vegetable as vermicides was proved scientifically and suggests that A. tricolor Linn plant leaves are valuable source of active compounds possessing anthelmintic activity. The preliminary phytochemical evaluation suggests the strong presence of glycosidic and phenolic substances in acetone extract may be responsible for its exceptional vermicidal activity. A further investigation is sought for the isolation and development of novel anthelmintic drug present in the plant. The data were verified as statistically significant by using one way ANOVA at 5 % level of significance (p < 0.05, n=3).